Problem solving skill of junior high school students on the solid geometry topic - F Rahmadeni; S Prabawanto; D Dasari (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study aims to investigate problem solving skills of junior high school students in solid geometry (cube, cuboid, prism, and pyramid) topic. A descriptive qualitative research study through individual written test (essay) was conducted to described problem solving skill of junior high school students. A test was given to 32 students of ninth grade in one of junior high school in Bengkulu, Indonesia. The result show that almost all student difficult to: 1) make strategy to solve the problem, 2) use the strategy planned before to solve the problem. This result of the study conclude that junior high school students have a low problem solving skills. The result of this study show us the need for developing an efffective learning which can fasilitate students in improving their problem solving skill.